2009
DOI: 10.1108/02652320910950187
|View full text |Cite
|
Sign up to set email alerts
|

Is branding creating shareholder wealth for banks?

Abstract: Purpose -The purpose of this article is to analyse, from a shareholder perspective, the link between branding and financial performance. The paper focuses, in the European context, on situations in which shareholder wealth is created or destroyed, and this is measured by using return on assets or market-to-book value as a performance benchmark. Design/methodology/approach -The investigation is designed as a quantitative study and is based on responses obtained from 847 listed banks including 480 located in Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…Ohnemus conducted a study on optimizing the amount of spending on the brand. Research conducted by this author showed that there is a point of equilibrium determining the optimum size of expenditures on the brand in relation to revenues (Ohnemus, 2009).…”
Section: Brands In Bankingmentioning
confidence: 98%
See 1 more Smart Citation
“…Ohnemus conducted a study on optimizing the amount of spending on the brand. Research conducted by this author showed that there is a point of equilibrium determining the optimum size of expenditures on the brand in relation to revenues (Ohnemus, 2009).…”
Section: Brands In Bankingmentioning
confidence: 98%
“…This is due to a number of circumstances, one of which was the realization of the untapped opportunities in this area in response to the emergence of a number of publications in the subject literature presenting brand performance measures (Chernatony et al, 2004) or proving the positive effect achieved by brands on bank performance (Ohnemus, 2009;Root, 2003). For example, one analysis shows that the average value of a bank's brand accounts for some 10% of its market capitalization, while in the case of companies offering durable consumer goods, it is around 35% (Shyder, 2012).…”
Section: Brands In Bankingmentioning
confidence: 99%
“…Branding is sales-related (Ohnemus, 2009) and plays a substantial role in developing strong brand equity (Song and Sung, 2013). Researchers have explored the effects of brand personality on variables such as consumers’ attitudes, perception of product quality, customer satisfaction and loyalty, purchase intentions, competitive advantage and financial performance (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Companies from the financial industry are selected as the research subjects in this study because this sector of industry has experienced an inevitable and dramatic shift with technology innovation and industry deregulation, which have intensified existing market competition (Ohnemus, 2009). After the 2008 global financial crisis and 2009 Eurozone crisis, financial companies become more pressured to build a trustworthy corporate brand both online and offline for risk-averse customers, and to gain long-term competitive advantages (Bravo et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…haft áhrif á tekjur þeirra. Í viðamestu rannsókn sem gerð hefur verið á tengslum ímyndar og arðsemi banka (Ohnemus, 2009) kom síðan í ljós að það var jákvaeð fylgni.…”
Section: Tafla 1 Svarmöguleikar Fyrir íMyndarmaelingu á Bankamarkaðiunclassified